2011
DOI: 10.1177/000313481107701149
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Carcinoma in Multinodular Goiter: Risk Factors

Abstract: The aim of the study was to analyze the frequency of incidental thyroid carcinoma (unknown tumor smaller than or equal to 10 mm) in a consecutive series of 462 total thyroidectomies for multinodular goiter and to investigate the clinical risk factors for this type of malignancy. A retrospective, single-center study of outcome data collected from patients with preoperative diagnosis of multinodular goiter who underwent total thyroidectomy at the General Surgery Unit of Pavia (Italy) between January 2000 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 20 publications
2
16
0
3
Order By: Relevance
“…Thyroid malignancy discovered incidentally in patients undergoing surgery for benign thyroid disease has also received a considerable amount of attention in the literature. Recent studies have documented an incidence of thyroid malignancy in these patients ranging from 7.1% to 12%, which is similar to the incidence reported in previous series of patients with PHPT . Autopsy studies have documented an incidence of occult thyroid malignancy ranging from 6.2% to 35.6% .…”
Section: Discussionsupporting
confidence: 84%
“…Thyroid malignancy discovered incidentally in patients undergoing surgery for benign thyroid disease has also received a considerable amount of attention in the literature. Recent studies have documented an incidence of thyroid malignancy in these patients ranging from 7.1% to 12%, which is similar to the incidence reported in previous series of patients with PHPT . Autopsy studies have documented an incidence of occult thyroid malignancy ranging from 6.2% to 35.6% .…”
Section: Discussionsupporting
confidence: 84%
“…With the widespread use of ultrasonography machines in clinical practice, thyroid nodules are being discovered with increasing frequency (15) . Studies have shown that many risk factors may affect the development of nodules in women (16,17) . The most current studies focus on thyroid nodules in women.…”
Section: Discussionmentioning
confidence: 99%
“…Our first case was misdiagnosed as a nodular goiter. A study has shown that the clinical risk factors for incidental carcinoma in a multinodular goiter are the presence of a dominant nodule in the goiter, hyperthyroidism, previous thyroid surgery, and calcification in the goiter, as shown on neck sonography or chest radiography . Therefore, a dominant nodule in a multinodular goiter with heterogeneously hypoechoic macrocalcification, no internal color Doppler signal, and possible cervical lymph node involvement in elderly women may be suggestive of malignant fibrous histiocytoma of the thyroid, especially with a rapidly enlarging mass exceeding 4 cm.…”
Section: Discussionmentioning
confidence: 99%